Driving Sustainable Growth: The Key Success Factors of a Bank in Malaysia - Liem Gai Sin; Ng Wei Chien; Jia Xin Liu; Wei Chen Li; Li Xin Zhang; Xin Tong Li; Yue Fei Sun; A.J. Ali; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
In today's fast-paced era, it is very important to maintain the awareness of sustainable development, and this awareness is particularly important in the development of banks. Hong Leong Bank is a multinational bank in Malaysia and one of the top five banks in Malaysia. It currently has more than 300 branches in Malaysia. The bank is technology-focused and focused on financial capabilities to serve customers in five regions. To develop better, the Bank must consider sustainable development strategies. Our research surveys and data combine to explore what kind of sustainability strategy the company implements to enable successful sustainable development. Through a sample questionnaire survey, we investigated how more than 100 banks from all walks of life are sustainable. The survey shows that it should be discussed from the perspective of the customer. First, environmental and social responsibility, pay attention to integrity, cherish employees, and integrate into the community. Our study highlights the need for a sustainability strategy in banks and explores the key factors for the successful development of Hong Leong Bank, which will help to improve the company's future development and user experience.